Pengaruh Reformasi Martin Luther Terhadap Gereja dan Dunia Kristen - Adelia Tamo Ina; Malik Bambangan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The Reformation led by Martin Luther in the 16th century was one of the most influential events in the history of the church and the Christian world. This research aims to analyze the impact of Martin Luther’s Reformation on the church and the Christian world as a whole. Luther, through his 95 Theses, challenged the authority of the Catholic Church, particularly regarding the sale of indulgences, and emphasized the doctrines of salvation by faith alone (sola fide) and the authority of Scripture alone (sola scriptura). The result of this movement was the emergence of Protestant Christian denominations, a deep division between Catholicism and Protestantism, and reforms within the Catholic Church known as the Counter-Reformation. This study employs historical methods, analyzing relevant primary and secondary documents to understand the theological, social, and political impacts of Luther’s Reformation. The Reformation also brought significant changes in education, liturgical languages, and the church’s role in the socio-political life of European society. Overall, Martin Luther’s Reformation triggered a transformation in the structure of the church and Christian society that persists into the modern era.